Evaluasi Efektivitas Penggunaan Antibiotika pada Pasien Rawat Inap Penderita Infeksi Saluran Pernapasan Bawah di Rumah Sakit Panti Rapih Yogyakarta Periode Januari-Juni 2005 (Journal of Tropical Pharmacy and Chemistry, 2025)
The non-TBC lower respiratory infection is a kind of infection that can attack bronchus, bronchioles and lung, the clinical manifestation can chronicle and severe. Generally the caused in children is virus and bacteria while in adult is bacteria, which is using antibiotics in medical attention. The purpose of research is to find out the infection pattern and the kind of antibiotics and to evaluate the using antibiotics based on effectivity. The non-experimental research that was form in a retrospective survey was done through medical record of patient with the lower respiratory infection in the time limit of january-june 2005 in Panti Rapih Hospital. The using of antibiotics was surveyed from medical record then analyzed using quantitative descriptive and presented in percentage. The result was that the most infection from patient with lower respiratory infection is bronchitis 45 % from 132 patients with 137 cases, the biggest percentage is man 58 % and placed in children age between 0-14 years old 52 % with the length of medical attention 6 days in average. Based on this  research 95 % gave clinical respond of fever decerease within 2-6 days and 45 % showed heal conditions, 40 % better, 10 % not heal and 5 % died.